2020
DOI: 10.3389/fmicb.2020.01452
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Factors and HIV Infection With Innate Cytokine Responses of Delivering Mothers and Newborns in Mozambique

Abstract: Maternal factors and exposure to pathogens have an impact on infant health. For instance, HIV exposed but uninfected infants have higher morbidity and mortality than HIV unexposed infants. Innate responses are the first line of defense and orchestrate the subsequent adaptive immune response and are especially relevant in newborns. To determine the association of maternal HIV infection with maternal and newborn innate immunity we analyzed the cytokine responses upon pattern recognition receptor (PRR) stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Mothers carrying a male fetus had higher concentrations of EGF, IL-15 and IL-7 cytokines, and induced higher antibody levels against SARS-CoV-2 than those carrying a female, but IgG transfer to the fetus was less efficient in the first ones. Previous studies have shown that fetal sex influences maternal serum cytokine and antibody profiles ( 55 57 ). In the context of SARS-CoV-2 infection, a recent study has reported similar results to ours, and a more pronounced SARS-CoV-2-specific antibody glycosylation in mothers carrying a male fetus, which would explain the reduced transplacental transfer ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mothers carrying a male fetus had higher concentrations of EGF, IL-15 and IL-7 cytokines, and induced higher antibody levels against SARS-CoV-2 than those carrying a female, but IgG transfer to the fetus was less efficient in the first ones. Previous studies have shown that fetal sex influences maternal serum cytokine and antibody profiles ( 55 57 ). In the context of SARS-CoV-2 infection, a recent study has reported similar results to ours, and a more pronounced SARS-CoV-2-specific antibody glycosylation in mothers carrying a male fetus, which would explain the reduced transplacental transfer ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable overlap and crosstalk between Th1 and Th2 responses, limiting the utility of this dichotomy 41 . Unfortunately, we were also unable to measure cytokines in the placental blood compartment 29 .…”
Section: Discussionmentioning
confidence: 98%
“…Overall, we found weak correlations between cytokine concentrations in maternal and umbilical cord plasma, supporting the lack of active placental regulation of cytokine production in umbilical cord, compared to maternal, blood. However, a 2020 study of cytokine responses in laboratory-stimulated blood samples from Mozambican mother-infant pairs, both with and without HIV, found a positive correlation between maternal and infant responses, suggesting a stronger association between maternal and offspring responses outside of the in utero period 29 . Furthermore, they observed that HIV infection affected the placental blood response, resulting in significantly heightened pro-inflammatory, Th1, and Th17 responses in individuals with HIV who did not receive ART before pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 ] Prominent among the theories is through the pro-inflammatory process induced by high levels of interleukin-2 (IL-2), IL-6, and tumor necrosis factor-alpha due to HIV infection. [ 7 ] Before introducing ART for the treatment of HIV, studies reported the link between HIV and LBW. [ 8 9 ] However, after the initiation of widespread ART, the effects of HIV infection on birth weight became more challenging to assess partly due to the differences in the timing of ART initiation, type of ART, and adherence challenges.…”
Section: Introductionmentioning
confidence: 99%